Secretion, Localization, and Antibacterial Activity of TasA, a Bacillus subtilis Spore-Associated Protein - Stöver, Axel G. (American Society for Microbiology, 1999)
The synthesis and subcellular localization of the proteins that comprise the Bacillus subtilis spore are under a variety of complex controls. To better understand these controls, we have identified and characterized a 31-kDa sporulation protein, called TasA, which is secreted into the culture medium early in sporulation and is also incorporated into the spore. TasA synthesis begins approximately 30 min after the onset of sporulation and requires the sporulation transcription factor genes spo0H and spo0A. The first 81 nucleotides of tasA encode a 27-amino-acid sequence that resembles a signal peptide and which is missing from TasA isolated from a sporulating cell lysate. In B. subtilis cells unable to synthesize the signal peptidase SipW, TasA is not secreted, nor is it incorporated into spores. Cells unable to produce SipW produce a 34-kDa form of TasA, consistent with a failure to remove the N-terminal 27 amino acids. In cells engineered to express sipW and tasA during exponential growth, TasA migrates as a 31-kDa species and is secreted into the culture medium. These results indicate that SipW plays a crucial role in the export of TasA out of the cell and its incorporation into spores. Although TasA is dispensable for sporulation under laboratory conditions, we find that TasA has a broad-spectrum antibacterial activity. We discuss the possibility that during the beginning of sporulation as well as later, during germination, TasA inhibits other organisms in the environment, thus conferring a competitive advantage to the spore.